Evaluation on flow discharge of grassed swale in lowland area - Mustaffa, Nurhazirah; Ahmad, Noor Aliza; Mohammad Razi, Mohd Adib (EDP Sciences, 2017)
Grassed swale is an open vegetated channel designed specifically in attenuating stormwater runoff to decrease the velocity, to reduce the peak flows, and minimize the causes of flood. Therefore, the fundamental of this study is to evaluate the flow discharge of swale in Universiti Tun Hussein Onn Malaysia (UTHM), which has flat land surface area. There are two sites of study were involved to assess the performance of swale as stormwater quantity control, named as swale 1 and swale 2. Data collection was conducted on 100 meters of length for each swale. The velocity of swale was measured thrice by using a current meter according to the six-tenths depth method, after a rainfall event. The discharge of drainage area in UTHM was determined by the Rational Method (Qpeak), and the discharge of swales (Qswale) was evaluated by the Mean-Section Method. Manning’s roughness coefficient and the infiltration rate were also determined in order to describe the characteristics of swale, which contributing factors for the effectiveness of swale. The results shown that Qswale is greater than Qpeak at swale 1 and swale 2, which according to the Second Edition of MSMA, the swales are efficient as stormwater quantity control in preventing flash flood at the campus area of UTHM.